THE BENEFITS OF CHLOROGENIC ACID AND ITS METABOLITES IN COMMON PATHOLOGIC FEATURES RELATED TO ALZHEIMER AND PARKINSON’S DISEASES DEVELOPMENT - Torres, Mayara Pinheiro (2025)
Chlorogenic acids (CGAs) are polyphenolic compounds of plant origin and found in high concentrations in beverages consumed around the world, such as coffee. CGAs are synthesized from the esterification reaction between caffeic acid (CFA) and quinic acid (QA), which can form 3 isomers (3-CQA, 4-CQA and 5-CQA). However, CGAs are thermosensitive compounds, which means that they are lost when exposed to high temperatures. This occurs, frequently, during the coffee beans roasting process, leaving only compounds resistant to high temperatures, such as caffeine. Recent studies have shown a protective effect of these compounds on the central nervous system, mainly through the increase in cellular antioxidant activity triggered by the activation of erythroid nuclear factor 2 related to factor 2 (Nrf2), and anti-inflammatory effect, promoting the decrease of inflammatory factors, such as nitric oxide (NO) and pro-inflammatory cytokines. The development of Alzheimer's and Parkinson's diseases are often associated with the accumulation of reactive oxygen species (ROS) and an increase in pro-inflammatory cytokines with a consequent increase in microglial activation. These events lead to cellular stress and intracellular damage, such as mitochondrial dysfunction, which further increase the accumulation of ROS, causing oxidative stress, damage to calcium homeostasis, activation of caspases related to apoptosis and subsequent death of these neurons. However, studies have increasingly shown that CGA is a promising agent against these events that lead to the progression of these two neurodegenerative diseases. Therefore, this work aimed to review the effects of CGAs on common characteristics responsible for the development of Alzheimer's and Parkinson's disease.